Efforts to Reduce Violence Against Children - Erianjoni Erianjoni; Yurni Suasti; Erniwati Erniwati; Fatmariza Fatmariza; Chici Cania Afdani; Alfajri Yusra (Postgraduate School, Universitas Negeri Padang, 2024)
Nagari Toboh Ketek, Enam Lingkung Sub-district, Padang Pariaman Regency is one of the Nagari appointed by the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia as the implementer of the Women's Friendly and Child Care Village (DRPPA) 2022 Nagari pilot project as a village implementing DRPPA, Nagari Toboh Ketek needs assistance from Universities. However, Nagari Toboh Ketek has not implemented Gender Mainstreaming (PUG) and Children's Rights Mainstreaming (PUHA) because it has not prepared a gender-responsive development plan and budgeting for Nagari (PUG/PPRG). So the Nagari does not yet have gender-responsive policies, programs, or budgeting. Universities provide this assistance with the Center for Gender and Development Research as the leading sector. Year 1 DRPPA mentoring activities have successfully carried out outreach activities, training, and workshops as well as assistance in preparing Nagari policies, programs, and activities related to DRPPA. Thus, Nagari already has several supporting programs in developing DRPPA. In the second year, the next activities are 1) Assistance in compiling Nagari data in a disaggregated manner based on gender (Nagari gender profile based on Sustainable Development Goals (SDGs) data); 2) Workshop on strengthening the capacity of Nagari government officials in gender-responsive planning and budgeting of the Nagari APB; and 3) Facilitation of educational information communication media in strengthening Nagari DRPPA.